Next-Generation Retailing In India: An Empirical Study Using Factor Analysis - Dash, Manju Smita; Krishna, C.V. (International Review of Management and Marketing, 2011)
The retail landscape in India is changing rapidly and is being scrutinized by large scale investments by foreign and domestic players. Market liberalization and changing consumer behaviour have sown the seeds of a retail transformation. Indian retailing is growing fast and imparting the consumer preferences across the country. Today retailing is largest contributing sector to country’s GDP i.e. 10% as compared to 8% in China, 6% in Brazil. Modern retailing is capable of generating employment opportunities for 2.5 million people by 2010 in various retail operations and over 10 million additional workforces in retail support activities. Organised retail which presently account for only 4-6 percent of the total market is likely to increase its share to over 30% by 2013.It offers huge potential for growth in coming years. India is becoming most favoured retail destination in the world.